EFOCUS 2: A randomised crossover trial of smartphone fundoscopy and direct ophthalmoscopy aiming to improve optic disc interpretation by medical students with e‐learning support. (8th August 2021) - Dunn, Hamish P.; Marks, Samuel; Teo, Kai Z.; Dunn, Stewart M.; Healey, Paul R.; White, Andrew J.
Abstract: Background: Ophthalmoscopy and its interpretation are complex. We aimed to compare the diagnostic accuracy of smartphone fundoscopy with traditional direct ophthalmoscopy for optic disc interpretation, with e‐learning support. Methods: We conducted a randomised, crossover study of 102 medical students. Students were offered e‐learning for optic disc interpretation. A fundoscopy objective structured clinical examination was conducted after an introductory lecture and 10‐min practical training session on smartphone fundoscopy and traditional ophthalmoscopy. Participants examined patients and simulator slides with a randomised crossover between smartphone [D‐eye (Padova, Italy) or iExaminer (Welch Allyn, Macquarie Park, Australia)] and traditional ophthalmoscopy (Welch Allyn). Optic discs were graded independently by three masked ophthalmologists. The primary outcome was the ability to interpret an optic disc as normal or abnormal. Secondary outcomes included other optic disc aspects; student preferences; and e‐learning performance. Results: Students' agreement with the gold standard for an abnormal or normal disc was significantly greater using a smartphone (74.4%) than with direct ophthalmoscopy (68.1%, p  = 0.032). More students preferred smartphone (74%) over direct ophthalmoscopy (26%, p  < 0.001). E‐learning led to an improvement in optic disc interpretation scores (mean improvement = 4.5%, 95% CI = 3.7–5.2, p  < 0.001). Conclusions: Medical students are more accurate at recognising an abnormal optic disc using smartphone fundoscopy than traditional direct ophthalmoscopy, and have a strong preference for smartphone fundoscopy. E‐learning may improve the interpretation of optic disc abnormalities. Smartphone fundoscopy may mitigate some technical challenges of fundoscopy and reinvigorate use of this valuable clinical examination.